2006
DOI: 10.1108/17415650680000068
|View full text |Cite
|
Sign up to set email alerts
|

Participatory design of learning media: Designing educational computer games with and for teenagers

Abstract: This paper reports on how prospective users may be involved in the design of entertaining educational computer games. The paper illustrates an approach, which combines traditional Participatory Design methods in an applicable way for this type of design. Results illuminate the users’ important contribution during game development, especially when intended for a specific target group. Unless prospective members of the target group are consulted it is difficult to foresee opinions of game content, aesthetics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 25 publications
0
49
1
1
Order By: Relevance
“…participatory design, [44]) allows the identification of significant gender-related preferences for a given purpose (target age, subject matter etc.). This ensures acceptability of design and the implementation of relevant adaptation aspects, thus contributing to learners' engagement and successful learning throughout the game.…”
Section: Resultsmentioning
confidence: 99%
“…participatory design, [44]) allows the identification of significant gender-related preferences for a given purpose (target age, subject matter etc.). This ensures acceptability of design and the implementation of relevant adaptation aspects, thus contributing to learners' engagement and successful learning throughout the game.…”
Section: Resultsmentioning
confidence: 99%
“…The game is targeted for the general population of children that have not been diagnosed with behavior disorders or mental health conditions. Participatory design was the approach adopted in the early part of the design, involving 10-year old children as users, testers, informants, and design partners [Druin 2002;Danielsson and Wiberg 2006]. …”
Section: Introductionmentioning
confidence: 99%
“…It is generally acknowledged that fun is an important design requirement for computer games, although there has been some critical debate about how possible it is to foresee the motivational factors for gaming (Danielsson & Wiberg, 2006). In this study, fun aspects were identified from children's designs and incorporated into the serious game that was developed based on their drawings.…”
Section: Discussionmentioning
confidence: 99%